Implementation of Islamic Principles of Corporate Governance Guidelines for Charity Health of Muhammadiyah - Dian Berkah (Sharia and Law Faculty, 2017)
The development of corporate governance issues continue to grow up to be a concern for Islamic studies scholars. There are those that directly analyze corporate governance in Islamic perspective, so the term is found on Islamic corporate governance. Furthermore, the developing corporate governance in the field of clinical as initial of clinical governance. But in its development, no studies have analyzed the clinical governance from the perspective of Islam, so it would appear a Islamic clinical Governance. This study seeks to identify the governance of Muhammadiyah charitable efforts in Indonesia engaged in the field of health by using the library based study method that is a part of the qualitative research approach. The paper found the history of the charitable efforts of health Muhammadiyah, the guiding principles of Muhammadiyah charitable health effort and the Islamic concept of clinical governance. Muhammadiyah is chosen for several reasons. Firstly, the Muhammadiyah organization in Indonesia that has a network to village level. Secondly, the first Islamic organization Muhammadiyah engaged in the business of charity health. Thirdly, the Islamic organization Muhammadiyah charitable health efforts that havespread throughout every region in Indonesia. Fourthly, Muhammadiyah has governance guidelines charitable efforts such as PedomanAmal Usaha Kesehatan, Pedoman Hidup Islami Warga Muhammadiyah (PHIWM) and Matan Keyakinan dan Cita-cita HidupMuhammadiyah (MKCHM) etc.